A Chlorhexidine Nanocarrier Strategy to Combat Oral Candidiasis Microcosm Biofilms - Cabral, Leandro Pimentel [UNESP]; Pessan, Juliano Pelim [UNESP]; Sampaio, Caio [UNESP]; do Prado, Rosana Leal; Hosida, Thayse Yumi [UNESP]; Sonoda, Celso Koogi [UNESP]; Monteiro, Douglas Roberto [UNESP] (MDPI, 2025)
Background/Objectives: Nanotherapies are a strategy to combat Candida resistance. This study analyzed the impacts of iron oxide nanoparticles (IONPs) functionalized with a chitosan (CS) layer acting as carriers of chlorhexidine (CHX) on an oral candidiasis microcosm biofilm. Methods: Saliva samples from three healthy donors were used to form biofilms, to which Candida species were added to reproduce an oral candidiasis microcosm. Biofilms were cultivated for 72 h on glass coverslips using an active adhesion model. Biofilms without Candida served as a control model. The nanocarrier loaded with CHX at 78 (IONPs-CS-CHX78) or 156 µg/mL (IONPs-CS-CHX156) was co-incubated with the biofilms for 24 h. Controls included isolated IONPs, CS, and CHX, in addition to an untreated group (NC). Assays for biomass production, metabolism, microbial load, and lactic acid production were conducted to assess antibiofilm effects. Biofilm structure, viability, and thickness were also examined by confocal microscopy. Statistical analysis was performed using one-way ANOVA or Kruskal-Wallis, subsequently accompanied by the Student-Newman-Keuls post hoc test (p < 0.05). Results: CHX and IONPs-CS-CHX156 were the most effective agents against all tested biofilm models, significantly reducing metabolism, microbial load (bacterial and fungal), and viability. For the oral candidiasis biofilm, the nanocarrier did not affect biomass or biofilm thickness but led to a significant increase in lactic acid levels compared to NC. Conclusions: It is concluded that the nanocarrier of CHX exhibits a significant reducing effect on oral candidiasis microcosm biofilms at half the concentration required for non-carried CHX. This nanostructure can be explored in the development of antiseptic or disinfectant solutions for managing oral candidiasis.